Transformed mucosa‐associated lymphoid tissue lymphomas: A single institution retrospective study including polymerase chain reaction‐based clonality analysis. (24th May 2019) - Kiesewetter, Barbara; Lamm, Wolfgang; Dolak, Werner; Lukas, Julius; Mayerhoefer, Marius E.; Weber, Michael; Schiefer, Ana‐Iris; Kornauth, Christoph; Bayer, Günther; Simonitsch‐Klupp, Ingrid; Raderer, Markus
Abstract: Given the lack of consistent data regarding the clinico‐pathological features and clonal lymphomagenesis of patients with mucosa‐associated lymphoid tissue (MALT) lymphoma and histological transformation (HT), we have systematically analysed 379 patients (32% gastric, 68% extra‐gastric; median follow‐up 52 months) diagnosed with HT at the Medical University Vienna 1999–2017, and reassessed tissues of identified patients by polymerase chain reaction (PCR)‐based clonality analysis. HT was documented in 12/379 patients (3·2%) and occurred at a median time of 22 months (range; 6–202 months) after diagnosis of MALT lymphoma. By PCR‐based clonality analysis, we detected a clear‐cut clonal relationship of MALT lymphoma and diffuse large B‐cell lymphoma (DLBCL) in 8 of 11 analysed cases proving that the large majority of DLBCL following MALT lymphoma are clonally‐related and constitute a real transformation. Interestingly, HT occurred within the first 2·5 years after diagnosis in patients with clonal relationship, whereas time to aggressive lymphoma was longer in patients identified as clonally‐unrelated (most likely secondary) lymphoma (82–202 months), suggesting that HT is an early event in this disease. Survival of patients with HT was poor with 6/12 dying at 1·5–33 months after HT, however, patients with localized gastric transformation had a superior outcome with only 1/6 dying due to progression of lymphoma.